Mechanism of podophyllotoxin-induced ovarian toxicity via the AMPK/TSC1/mTOR/ULK1 axis in rats on the basis of toxicological evidence chain (TEC) concept - Jingjing Li; Yanzhao Zhang; Mingyue Wei; Junjie He; Huifeng Ma; Zilong Chen; Jiajia Duan; Chuanxin Liu (Ecotoxicology and Environmental Safety)
Background: Podophyllotoxin is a compound with clinical effects, such as anticancer and antiacromegaly effects, but its systemic toxicity has led to extremely limited clinical application. Methods: Using the toxicological evidence chain (TEC) as a research method, our team constructed, for the first time, a rat model in which podophyllotoxin caused ovarian damage and investigated the mechanism of the toxic effects of podophyllotoxin on the ovaries. Results: The rats presented different degrees of diarrhoea, body surface bruising, and petechiae, and the serum biochemical results revealed significant changes in the activities of the oxidative stress indicators SOD and MDA and the levels of the inflammatory indicators TNF-α and IL-1β. The pathological results suggested that the rat ovaries were significantly damaged, and the histological results revealed Th17 cell differentiation, necroptosis, Hspa9 expression, and other pathways or targets related to inflammation, necroptosis/apoptosis or autophagy. Conclusion: Podophyllotoxin exerts toxic effects by altering autophagy through the AMPK/TSC1/mTOR/ULK1 signalling pathway. This study provides new insights into the mechanism of the toxic effects of podophyllotoxin and new ideas for the clinical application of podophyllotoxin.